2015
DOI: 10.3329/jdmc.v23i1.22706
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hepatic Tuberculosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It accounted for 5.4% of all tuberculosis cases admitted in the institution during the study period which is higher than the 1.2% of diagnosed TB patients at a hospital in South Africa. 10 The Philippine General Hospital is a tertiary medical center where patients with more severe liver conditions are referred. In 2010, tuberculosis was the sixth leading cause of death (26.3 deaths/100,000 population) 8 in the country and was the third highest cause of mortality among immunizable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It accounted for 5.4% of all tuberculosis cases admitted in the institution during the study period which is higher than the 1.2% of diagnosed TB patients at a hospital in South Africa. 10 The Philippine General Hospital is a tertiary medical center where patients with more severe liver conditions are referred. In 2010, tuberculosis was the sixth leading cause of death (26.3 deaths/100,000 population) 8 in the country and was the third highest cause of mortality among immunizable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In focal tuberculosis, large tumor-like tuberculoma is formed by coalesces of various size granuloma. Caseating and liquefaction necrosis occur within tubercular granuloma and to form tubercular abscess [3] (Figures 1& 2). In world literature, 30-50 years are the common age group and usually presents with fever (50-90%), abdominal pain (45-66%), and hepatomegaly in localized hepatic TB [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Presenting symptoms in these settings are mainly those of military tuberculosis [2]. A South African study showed that hepatic tuberculosis considered for 1.2% of all cases of tuberculosis diagnosed at a general hospital [3]. In Bangladesh, there are few cases of hepatic tuberculosis reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…It is more difficult for a clinician to diagnose as in most cases it is frequently confused with pyogenic or amoebic liver abscess or a hepatoma [3]. Only a few cases have been reported in Bangladesh till date [4][5][6][7]. Recently we came across tubercular liver abscess in an immunocompromised patient without any primary foci of infection which was really a diagnostic challenge for us.…”
mentioning
confidence: 99%